EFFECT OF Camelia sinensis SUPPLEMENTATION ON GROWTH PERFORMANCE, CARCASS COMPOSITION AND HAEMATOLOGICAL PARAMETERS OF Coptodon zillii JUVENILES - Oladipupo, T. M; Salami, S.R (Nigerian Journal of Fisheries, 2024)
The present study aimed at assessing how varying levels of Camellia sinensis in the diets affected the growth of Coptodon zillii juveniles for 70 days. Five iso-proteinous diets (35% CP) were prepared for C. zillii fingerlings, each containing different amounts of C. sinensis leaf meal (0.0, 0.5, 1.0, 1.5, and 2.0 g/100g), labeled as D1-D5 respectively. The diet containing 0.0g/kg of C. sinensis leaves meal serves as the control without any inclusion of additives. Two hundred and twenty-five C. zillii juveniles, with an average weight of 9.39±0.01g, were randomly allocated to 15 glass tanks (70 liters each, measuring 70cm x 45cm x 45cm) at a rate of 15 fish per tank, representing four treatments and one control with three replicates each. Results indicated that the highest weight gain was recorded in fish fed with D4, while the lowest was in those fed the control diet. The best result in terms of FCR was recorded in D4 while the poorest value was recorded in D1. The highest value of WBC was recorded in fish fed D5 while the lowest value was recorded in fish fed D1. The highest value of RBC, PCV and Hb was recorded in D2 while the lowest value was recorded in D5. Fish fed D4 had the highest crude protein while fish fed D1 had the lowest. In conclusion, the study suggests that including 1.5g/100g of C. sinensis leaf meal in the diet of C. zillii is optimal for enhancing growth performance without adverse effects on carcass composition and haematological parameters.